(NpROBLEMY MONITORINGA I OHRANY OKRUVA@]EJ SREDY (B:s (NtRUDY (BI (NSOWETSKO(B-(NKANADSKOGO SIMPOZIUMA sssr(B, (NtBILISI(B, 11-17 (NAPRELQ (B1988 (NG(B. /s - (NiZRA\LX(B, (N`RIJ aNTONIEWI^s ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
(Nw NADZAG(B.: (NgOS(B. (NKOM(B. (Nsssr PO GIDROMETEOROLOGIIs
Keywords: (NmONITORING OKRUVA@]EJ SREDYs; (NoHRANA OKRUVA@]EJ SREDYs